Distinct bacterial signature in the raw coal with different heating value - Zou, Haijiang; Tian, Miaomiao; Xu, Jianmin; Li, Guowei; Chen, Hui; Yang, Junjun; Ling, Pengtao; Shen, Zhenxing; Guo, Siyu (Frontiers in Microbiology, 2024)
Coal represents a significant natural resource in our world, and its quality and commercial value is primarily determined by its heating capacity. Numerous scientists worldwide have attempted to explore the impact of various environmental factors on coal rank, yet their conclusions are often inconsistent. In this study, the Illumina MiSeq sequencing approach was used to analyze the bacterial community from a low-rank coal mine as well as a high-rank mine. Moreover, we investigated the relationship between the physical and chemical properties of the coal and the bacterial composition. Overall, we found that the high-rank coal exhibited higher heating value but higher total sulfur and lead levels. Considering the community of bacteria, the abundances of Phascolarctobacterium and Anaerostipes were highly elevated in the high-rank coal group. Most interestingly, the Anaerostipes abundance was correlated with coal quality positively. Additionally, the co-occurrence network of the bacterial community in the high-rank coal group showed much higher complexity. The bacterial functional potential predictions indicated elevated levels of phosphoenolpyruvate carboxykinase ATP, succinate dehydrogenase fumarate reductase flavoprotein subunit, and methylenetetrahydrofolate dehydrogenase NADP methenyltetrahydrofolate cyclohydrolase pathways. This study revealed that high-rank coal had more complicated co-occurrence network and elevated Anaerostipes abundance, which may suggest a potential biological pathway that can be explored to enhance coal quality.